PROBLEM-BASED LEARNING MODEL FOR THREE-PHASE INDUCTION MOTOR - Prastyaningrum, Ihtiari; Pratama, Hendrik (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2019)
This study aims to examine the Problem-Based Learning(PBL) model to improve the understanding of electromagnetic induction material in three-phase induction motor. Most of the students attending the Electrical Machine course have low understanding upon the working principles of the three-phase induction motor, in particular the basic theory of the relationship between the electromagnetic field and the three-phase induction motor. This study involved seventeen students of Electrical Engineering Education Study Program of Universitas PGRI Madiun in East Java. Data were collected through observation and tests, with the statistical test of research using paired sample t-test. This quasi-experimentresearch employed one-group pre-test and post-test design. The results showed that the application of PBL model with video simulation and practicesimprove students?understanding of the materials. The learning process by utilizing simulated animation video and the practices of unloading three-phase induction motors directly, the students?understanding of the working principles of three-phase induction motors increases with the average of N-Gain score. These results indicate the use of video and hands-on practice become effective way to deliver complex and abstract material to students. It is also believed that the learning on electromagnetic induction can be carried out more efficiently. Additionally, such learning model is believed to ease physics education.